Physical activity influences adherence to pharmacological treatments in patients with severe mental disorders: results from the multicentric, randomized controlled LIFESTYLE trial - Sampogna, Gaia; Luciano, Mario; Di Vincenzo, Matteo; Toni, Claudia; D’Ambrosio, Enrico; Rampino, Antonio; Rossi, Alessandro; Rossi, Rodolfo; Amore, Mario; Calcagno, Pietro; Siracusano, Alberto; Niolu, Cinzia; et al. (Frontiers in Pharmacology, 2023)
Poor adherence to pharmacological treatment is frequent in people with severe mental disorders and it often causes lack of effectiveness of many psychotropic drugs. Thus, efforts should be made to improve adherence to pharmacological treatments in patients with these disorders.In this paper, based on the LIFESTYLE randomized, controlled multicentric trial, we aim to:1) assess the level of adherence in a real-world sample of patients with severe mental disorders; 2) evaluate differences in treatment adherence according to patients' sociodemographic and clinical characteristics; 3) evaluate the impact of an innovative psychosocial intervention, on patients' adherence to treatments. The Lifestyle Psychosocial Group Intervention consists of group sessions, focused on different lifestyle behaviours, including healthy diet; physical activity; smoking habits; medication adherence; risky behaviours; and regular circadian rhythms. At end of each session a 20-min moderate physical activity is performed by the whole groupThe sample consists of 402 patients, mainly female (57.1%, N=229), with a mean age of 45.6 years (±11.8). Less than 40% of patients reported a good adherence to pharmacological treatments. Adherence to treatments was not influenced by gender, age, diagnosis and duration of illness. At the end of the intervention, patients receiving the experimental intervention reported a significant improvement in the levels of adherence to treatments (T0: 35.8% vs. T3: 47.6%, p<.005).Patients practicing moderate physical activity reported a two-point improvement in the levels of adherence (odds ratio [OR]: 1,542; 95% confidence intervals [CI]: 1,157-2,055; p < 0.001), even after controlling for several confounding factors.The experimental lifestyle intervention, which can be easily implemented in the routine clinical practice of mental health centres, was effective in improving adherence to pharmacological treatments.